The adjective: an eminently syncategorematic part of speech - Goes, Jan (Kalbotyra, 2021)
In this article we propose an alternative to the theories which subdivide the adjective into three major types (qualifier, relational, adjective of the third type), themselves subdivided into several subclasses. We believe instead that there is only one adjectival lexeme with different uses (unitary hypothesis). To do this, we start from the two ways of looking for the adjectival prototype: on the one hand, the abstract prototype built by accumulating criteria, on the other, the semantic prototype. We examine the behavior of occurrences of the abstract prototype (admirable, monumental) and the semantic prototype (grand) with respect to gradation, the attributive function (more specifically the place of the adjective) and the predicative function. The examples show not only that the two prototype models can be reconciled, but above all that the behavior and the meaning of any adjective depend in large part on the noun it qualifies, a result which confirms our unitary hypothesis. The syntactic-semantic dependence of the adjective on the supporting substantive is such that it can be concluded that the adjective is a syncategorematic part of speech, rather than a polysemous one.